MR-compatible loading device for assessment of heel pad internal tissue displacements under shearing load. (December 2021) - Trebbi, Alessio; Perrier, Antoine; Bailet, Mathieu; Payan, Yohan
Highlights: Shearing and normal loadings can be applied and measured in a MR compatible environment by means of springs in polylactide. Image registration can be used to calculate displacement maps between 3D images representing an unloaded and a loaded configuration. A shear load of 12 N is sufficient to generate significant displacements in the soft tissues of the human heel. A device made in Teflon, polylactide and nylon has been proposed to apply and measure shearing and normal loadings. This device does not generate any artifacts in MR acquisitions. Abstract: In the last decade, the role of shearing loads has been increasingly suspected to play a determinant impact in the formation of deep pressure ulcers. In vivo observations of such deformations are complex to obtain. Previous studies only provide global measurements of such deformations without getting the quantitative values of the loads that generate these deformations. To study the role that shearing loads have in the etiology of heel pressure ulcers, an MR-compatible device for the application of shearing and normal loads was designed. Magnetic resonance imaging is a key feature that allows to monitor deformations of soft tissues after loading in a non-invasive way. Measuring applied forces in an MR-environment is challenging due to the impossibility to use magnetic materials. In our device, forces are applied through the compression of springs made of polylactide. Shearing and normal loads were applied on the plantar skin of the human heel through a flat plate while acquiring MR images. The device materials did not introduce any imaging artifact and allowed for high quality MR deformation measurements of the internal components of the heel. The obtained subject-specific results are an original data set that can be used in validations for Finite Element analysis and therefore contribute to a better understanding of the factors involved in pressure ulcer development.